Annular Elastolytic Giant Cell Granuloma - A Rare Case with Systemic Involvement (Bangladesh Journal of Medical Science, 2016)
Annular elastolytic giant cell granuloma (AEGCG) is a rare granulomatous dermatosis characterized by loss of elastic fibers and elastophagocytosis by multinucleated giant cells. It is characterized by annular plaques that are similar to those observed in granuloma annulare but that specifically appear in sun-exposed skin and occurs more commonly in females than males. There have been reported cases of AEGCG associated with diabetes mellitus, systemic sarcoidosis, cutaneous amyloidosis, molluscum contagiosum, squamous cell carcinoma of the lung and cutaneous T-cell lymphoma. We report a case of AEGCG in both sun-exposed as well as covered areas of a middle aged lady with hepatic nodules and Barrets esophagus.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.488-491